THE EFFECT OF INDIRECT PAYMENT TO EMPLOYEES LOYALTY IN BANK PERKREDITAN SADYHA MUKTI PARAMA - Novadjaja, Lily Hendrasti; Ikhram W, M. Abdi Dzil (Department of Management, 2019)
This study aims to determine several dimensions of indirect compensation of on the job break, hazard protection, service programs, legal payments and health insurance is a dimension of indirect compensationThe population in the study were all employees of Bank Perkreditan Rakyat (BPR) Sadyha Mukti Parama, there are 16 employees. This study used questionnaire to be answered the analysis and the data analysis used Partial Least Square (PLS). Based on the analysis of data in this study show that the compensation indirect positive effect on employee loyalty. Substantially the results showed that the strongest indicator that supports variable indirect compensation to the loyalty of the employees are the programs of the employees. The programs of employees in the opinion of the respondents is paramount, this is because employees of Bank Perkreditan Rakyat (BPR) Sadyha Mukti Parama already find facilities such as a break on the Job, protection against danger, service programs, payment of legal and health insurance was considered enough to meet the needs. This study provides some theoretical implications indicate that the compensation does not directly provide a significant impact on employee loyalty Bank Perkreditan Rakyat (BPR) Sadyha Parama Mukti and the results show that the indirect compensation variable dimensions are on the job break, hazard protection, service programs, legal payments and health insurance have a significant effect on employee loyalty.